2013
DOI: 10.4103/0974-7753.122961
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal profile in Indian men with premature androgenetic alopecia

Abstract: Introduction:Alopecia in male is considered as a genetically determined disorder characterized by increased level of local androgen metabolite and increase androgen receptor binding in balding areas. Frequent deviations of hormones from normal values have been reported in men diagnosed with premature androgenetic alopecia (AGA) especially for androgens, gonadotropins and sex hormone binding globulin (SHBG). Different studies in the past have inferred that premature baldness before the age of thirty in males co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 21 publications
(29 reference statements)
18
26
0
1
Order By: Relevance
“…In our study, the mean value of testosterone in cases was significantly higher as compared to controls in agreement with studies by Narad et al [11], Schmidt et al [12] and Yildiaz et al [13]. However, Duskova et al [14] and Starka et al [15] showed subnormal levels of testosterone in their cases.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our study, the mean value of testosterone in cases was significantly higher as compared to controls in agreement with studies by Narad et al [11], Schmidt et al [12] and Yildiaz et al [13]. However, Duskova et al [14] and Starka et al [15] showed subnormal levels of testosterone in their cases.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings were noted by Duskova et al [14] and Narad et al [11] lower the levels of SHBG, higher the free testosterone and thus hyperandrogenism.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…[12][13][14] However, most authors have defined premature or early-onset alopecia as starting before age 30 years. 12,[16][17][18][19][20] According to most studies, patterned hair loss in men occurring before age 30 years is considered the phenotypic equivalent of PCOS. 5,6,9,10 Hence, the age group of 19 to 30 years was used in our study to define early AGA.…”
mentioning
confidence: 99%
“…It has also been recently proven that thyroid abnormalities are strongly associated with hair growth [8]. There is a putative role of glucocorticosteroids and prolactin in hair biology [9,10]. The role of parathyroid hormone (PTH) and abnormalities of parathyroid gland function in hair growth remains not well understood.…”
Section: Introductionmentioning
confidence: 99%